Mitoribosomal synthetic lethality overcomes multidrug resistance in MYC-driven neuroblastoma - Borankova, Karolina; Krchniakova, Maria; Leck, Lionel Y W; Kubistova, Adela; Neradil, Jakub; Jansson, Patric J; Hogarty, Michael D; Skoda, Jan (Cell death & disease, 2023)
Mitochondria are central for cancer responses to therapy-induced stress signals. Refractory tumors often show attenuated sensitivity to apoptotic signaling, yet clinically relevant molecular actors to target mitochondria-mediated resistance remain elusive. Here, we show that MYC-driven neuroblastoma cells rely on intact mitochondrial ribosome (mitoribosome) processivity and undergo cell death following pharmacological inhibition of mitochondrial translation, regardless of their multidrug/mitochondrial resistance and stem-like phenotypes. Mechanistically, inhibiting mitoribosomes induced the mitochondrial stress-activated integrated stress response (ISR), leading to downregulation of c-MYC/N-MYC proteins prior to neuroblastoma cell death, which could be both rescued by the ISR inhibitor ISRIB. The ISR blocks global protein synthesis and shifted the c-MYC/N-MYC turnover toward proteasomal degradation. Comparing models of various neuroectodermal tumors and normal fibroblasts revealed overexpression of MYC proteins phosphorylated at the degradation-promoting site T58 as a factor that predetermines vulnerability of MYC-driven neuroblastoma to mitoribosome inhibition. Reducing N-MYC levels in a neuroblastoma model with tunable MYCN expression mitigated cell death induction upon inhibition of mitochondrial translation and functionally validated the propensity of neuroblastoma cells for MYC-dependent cell death in response to the mitochondrial ISR. Notably, neuroblastoma cells failed to develop significant resistance to the mitoribosomal inhibitor doxycycline over a long-term repeated (pulsed) selection. Collectively, we identify mitochondrial translation machinery as a novel synthetic lethality target for multidrug-resistant MYC-driven tumors.
Keywords: Neuroblastoma; Proto-Oncogene Proteins c-myc; signální transdukce; protoonkogen n-myc; nádorové buněčné linie; Synthetic Lethal Mutations; Signal Transduction; apoptóza; Humans; Cell Line, Tumor; neuroblastom; N-Myc Proto-Oncogene Protein; protoonkogenní proteiny c-myc; umělé letální mutace; lidé; Apoptosis